Function of DNA polymerase I in RNA-primed synthesis of bacteriophage M-13 duplex DNA. - Schneck, P K (1976)
Cell-free extracts from Escherichia coli contain a DNA polymerase activity resistant to SH-blocking agents, which is capable of synthesizing complementary strand DNA on a circular M-13 DNA template by extension of RNA primers. This activity is considered to be identical with DNA polymerase I (or some altered form of this enzyme) since it is missing in extracts from po1A- cells. DNA synthesis in the presence of SH-blocking agents occurs at a reduced rate as compared to untreated controls and leads to the formation of DNA chains of defined size (0.4-0.5 genome's length). It is concluded that efficient M-13 duplex DNA synthesis requires the cooperation of both DNA polymerase I and III.